Effects of Perceptual Learning Styles on Chinese EFL Learners’ Writing Proficiency in the Reading-writing Integrated Continuation Task - Wang, Huafeng; Tu, Mengwei; Liang, Meiqiong (International Journal of Linguistics, 2022)
Previous studies have manifested that the reading-writing integrated continuation task has great language learning potential and linguistic alignment facilitated by the continuation task positively affects L2 learners’ written performance. As an individual difference construct, perceptual learning style has been investigated from its impact on EFL learning, while research on how it affects learners’ performance in the continuation task seems deficient. To this end, this study investigated the relationship between Chinese EFL learners’ perceptual learning style and writing proficiency in the reading-writing integrated continuation task. Participants were 46 intermediate learners of L2 English from two intact classes who were required to perform both independent topic writing and the continuation task. The results showed that 1) group and auditory style learners slightly outperformed on phrasal alignment while visual and tactile performed better on clausal alignment; 2) visual, tactile and auditory learners were likely to generate content-rich, well-organized and more accurate written production, but students’ linguistic fluency in topic writing outperformed that in the continuation task; 3) learners who prefer audio input showed in inferiority on the continuation writing. These findings confirm that perceptual learning style might be a mediator affecting learners’ linguistic alignment within the continuation task.